Bioethics on research with children and adolescents at risk: dilemmas about informed consent and confidentiality - Silva, Lucas Neiva; Lisboa, Carolina; Koller, Sílvia Helena (Brazilian Journal of Sexually Transmitted Diseases, 2005)
This paper analyzes the Bioethics principles applied to the dilemmas found in the researches with children and adolescents at personal and social risk. Firstly, it is presented a discussion about the general Bioethics principles applied to health-related researches with human subjects. The discussionspecifies issues on research and intervention with children and adolescents at risk in order to emphasize dilemmas and conflicts faced by professionals. They are analyzed situations in which it is not possible to obtain the Informed Consent from participants’ relatives. It may occurs in cases of children in street situation and children who are victims of physical and sexual abuse, whose parents do not accomplish the protective function. It is alsoanalyzed the need of maintaining or not the confidentiality when the research information reveals some risk to the participants. It is intended thatthese questions raise new discussions on the researcher’s practice about new dilemmas and research themes in health. Bioethics is presented as anarea that offers protection to the participants as well as confidence to the researchers that work with at-risk populations.